2009
DOI: 10.1093/her/cyp006
|View full text |Cite
|
Sign up to set email alerts
|

Computer-tailored dietary behaviour change interventions: a systematic review

Abstract: Improving dietary behaviours such as increasing fruit and vegetable consumption and reducing saturated fat intake are important in the promotion of better health. Computer tailoring has shown promise as a strategy to promote such behaviours. A narrative systematic review was conducted to describe the available evidence on ‘second’-generation computer-tailored primary prevention interventions for dietary behaviour change and to determine their effectiveness and key characteristics of success. Systematic literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 32 publications
5
114
2
Order By: Relevance
“…This is largely in line with the conclusions of recent reviews that found convincing evidence for the effectiveness of computer-tailored interventions on diet but inconclusive results for physical activity among adults. 5,6,8 …”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…This is largely in line with the conclusions of recent reviews that found convincing evidence for the effectiveness of computer-tailored interventions on diet but inconclusive results for physical activity among adults. 5,6,8 …”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,28,29 suggesting possible response bias. There is a need to examine further whether objectively measured colorectal cancer screening improves in response to sociopsychologi...…”
Section: Introductionmentioning
confidence: 99%
“…Some literature has focused on the potential for automisation, personalisation of information or prompts and the development of online support communities [7] (p. 330). A range of studies has explored the efficacy and potential of dietary and physical activity interventions through digital tools [8][9][10][11][12], and the wide-ranging implications of "Web 2.0" technologies have been surveyed [13]. Some ethnographic approaches to the use of information technologies in a healthcare setting have been attempted, in particular analysing the ways in which they are implicated in social practice [14], although this approach has not yet been taken to the more informal and commercial technologies and practices central to this study.…”
Section: Quantified Selfmentioning
confidence: 99%